Environmental enrichment affects immunity and reduces disease severity in pigs after co-infection, with stronger effects when applied from birth than from weaning - de Bruijn, Brigitte G. C.; van Dixhoorn, Ingrid Danielle Ellen; Bolhuis, J. Elizabeth; Cornelissen, Jan B. W. J.; Stockhofe-Zurwieden, Norbert; Kluivers, Marion; Rebel, Johanna M. J. (Frontiers in Veterinary Science, 2024)
We investigated whether environmental enrichment applied at different life stages of pigs affects the susceptibility to and severity of disease by studying immune cell functions around weaning and during nursery, the effects of infection in ex vivo models and in vivo using a co-infection model of Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) followed by an Actinobacillus pleuropneumoniae infection. Pigs were either conventionally housed (CCH) or enriched housed throughout life, with enrichment consisting of extra space, rooting materials and co-mingling with another litter before weaning (EEH), or they were switched from conventional to enriched housing at weaning (CEH). Sixty days after birth, ten pigs per treatment were infected with PRRSV followed by an A. pleuropneumoniae infection eight days later. Six other pigs per treatment were euthanized before their pen mates were exposed to the co-infection. From these piglets, bronchial-alveolar fluid was collected, and precision cut lung slices were taken to test the effect of the treatments in an in vitro infection model. At six days after weaning EEH pigs had higher whole blood cell counts and higher concentrations of IL1ß and TNFα than CCH and CEH pigs. In the ex vivo precision cut lung slice model no differences in cytokine response in lung tissue after infection with swine influenza or A. pleuropneumoniae were observed between treatments. After experimental co-infection the proportion of EEH pigs with lung lesions (3/10) tended to be lower than in CCH (8/10), with CEH (6/10) being in between. In conclusion, enriched housing from birth reduced disease severity to co-infection with PRRSV and A. pleuropneumoniae. Enrichment applied after weaning also seemed to decrease the pathological lung deviations to the co-infection as compared to barren housed pigs, but to a much lower extent.